Lindavia intermedia (Bacillariophyceae) and Nuisance lake Snow in New Zealand: Chitin Content and Quantitative PCR Methods to Estimate Cell Concentrations and Expression of Chitin Synthase1. Issue 5 (9th June 2020) - Novis, Phil M.; Sales, Ruth E.; Gordon, Keith; Manning, Nathan; Duleba, Mónika; Ács, Éva; Dressler, Mirko; Schallenberg, Marc
Abstract : Lake snow, caused by the freshwater centric diatom Lindavia intermedia, has become problematic in several large, oligotrophic New Zealand lakes over the past decade. Macroaggregates produced by L. intermedia foul fishing lines, intake screens, and water filters, and have a negative impact on recreational values. It was confirmed that the fibers constituting lake snow are composed of chitin, two chitin synthase genes ( chs 1 and 2) from L. intermedia were characterized, new qPCR‐based tools to quantify the abundance of the species and measure expression of chs 2 relative to the reference gene act 1 (the product of which has cytoskeletal functions) were developed. The strong heterogeneity and mucilaginous nature of lake snow samples create particular difficulties for calibrations of gene or transcript copy numbers with cell densities and obtaining high yields of mRNA. However, data collected from four lakes during November 2018 and February and May 2019 show that abundance of L. intermedia is always high when lake snow is also abundant, but that a full range of L. intermedia abundance can occur when lake snow is absent, suggesting that chitin production is not obligate in L. intermedia . This result is consistent with the available data for chs 2 expression, which suggest higher transcription when lake snow is abundant. Lake snow production by L. intermedia therefore requires an as yet undetermined stimulus independent of cell abundance.